How and when do conglomerates influence the creativity of their subsidiaries? - Rawley, Evan; Godart, Frédéric; Shipilov, Andrew (Strategic Management Journal, 2018)
[Research Summary: We develop a framework for understanding how and when membership in a conglomerate affects a subsidiary's creativity. Focusing on "sectoral" conglomerates with several subsidiaries in the same industry, we explain that the effect has two components: an imprinting effect at the time of affiliation, and a concurrent effect from ongoing interactions with other subsidiaries. In the context of the high-end fashion industry, we find that a subsidiary's creativity increases when it joins a conglomerate with either very low or high creativity. We interpret this as an imprinting effect of the environment inside a conglomerate on how effectively a subsidiary is integrated. Furthermore, over time, the creativity of a subsidiary increases with the creativity of other subsidiaries. The results provide evidence of creativity "spillovers" within conglomerates. Managerial Summary: We examine the role that fashion conglomerates like LVMH or Kering play in the creativity of their subsidiaries. These conglomerates create value through internal transfers of operational and creative practices. Some conglomerates are better at integrating subsidiaries after acquisition than the others: it seems that the better integrators are conglomerates that either have other creative subsidiaries or subsidiaries that lack creativity. Furthermore, conglomerates with other creative subsidiaries continuously improve the creativity of their member firms, probably due to their ability to transfer high-quality internal practices.]